2018
DOI: 10.1080/10408347.2017.1398063
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Analytical Methods for Determination of Ceftriaxone Sodium

Abstract: Ceftriaxone sodium is a third-generation semi-synthetic antibiotic belonging to the class of cephalosporins. Is administered only by parenteral route and has the ability to cross the blood-brain barrier. It has bactericidal action; its main activity is related to the Gram-negative bacteria, being also able to act against Gram-negative bacilli resistant to the first- and second-generation cephalosporins. The present study presents a survey of the characteristics, properties and analytical methods used for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 43 publications
0
14
0
3
Order By: Relevance
“…Studies in rabbits with meningitis have shown that the combination of ceftriaxone with trovafloxacin is synergistic against resistant penicillin Pneumococcus with an increase of about 1.85-fold relative to the bactericidal activity of the isolated antibiotics. (9,15,(19)(20)(21)(22)(23)…”
Section: Eficácia Comparativamentioning
confidence: 99%
See 3 more Smart Citations
“…Studies in rabbits with meningitis have shown that the combination of ceftriaxone with trovafloxacin is synergistic against resistant penicillin Pneumococcus with an increase of about 1.85-fold relative to the bactericidal activity of the isolated antibiotics. (9,15,(19)(20)(21)(22)(23)…”
Section: Eficácia Comparativamentioning
confidence: 99%
“…Plasma and urine concentration of ceftriaxone may be determined by a high-performance liquid chromatography method, according to Trautmann and Haefelfinger. (21,24) Ceftriaxone has a non-linear dose-dependent pharmacokinetics, since binding to plasma proteins is variable from 85 to 95% with the plasmatic antibiotic concentration. (12)…”
Section: Pharmacokinetics: Absorption Distribution Metabolization Amentioning
confidence: 99%
See 2 more Smart Citations
“…В основі спектрофотометричних методик визначення цефтріаксону у видимій ділянці спектра лежать такі реакції [2]: комплексоутворення з іонами металів; комплексоутворення з перенесенням заряду; азосполучення з фенольними сполуками [4,5]; редокс реакції; гідроліз та наступна взаємодія із забарвленими реагентами; утворення іонних асоціатів. Для визначення залишків цефтріаксону у біологічних тканинах та фізіологічних рідинах найчастіше використовують високоефективну рідинну хроматографію з масспектрометричним детектуванням [6].…”
unclassified